Modelling of thermoelectric generator with experimental investigation - Li, Jia Wen (Nanyang Technological University, 2021)
The thermoelectric effects, namely the Seebeck, Peltier and Thomson effects are inter-related to the transformation of thermal into electrical energy. The operation of the thermoelectric module for power generation is very simple. The thermoelectric generator possesses low commercial value due to its lower thermoelectric figure of merit or efficiency, which can be solved by the development of thermoelectric materials or the recovery of waste-heat generated during thermoelectric operation or Joule heating. Therefore, the proposed final year project deals with the development of thermoelectric generator (TEG) that can be applied to recover Joule heating during its pulse and non-pulse modes of cyclic operation. The objective is to investigate experimentally the performances of the TEG ranging from dynamic to steady state conditions. Thermoelectric generators are environmentally friendly with many advantages including the absence of moving parts, requiring only low maintenance and high scalability. At first, the experimental test rig is developed, and fabricated and detailed experiments are performed for various heating energy applied to the TEG. During experimentation, both the steady-state heating and several variations of pulsed heating are conducted. For the same energy input, the thermoelectric generator is found to perform better with pulsed heating as compared to steady-state heating. Duty cycles are varied during pulsed heating to determine their effects on the performances (in terms of output electric power and efficiency) of the thermoelectric generators. Lower duty cycles result in greater improvement in efficiencies as compared to the steady-state efficiencies for the same energy input. The optimal low-state time for pulsed heating within a range of hot-side and cold-side temperature of the thermoelectric module is also obtained to be around 6 minutes.